Status of Arbuscular Mycorridzal Colonization in Certain Tropical Forest Tree Legume Seedlings - Rahman, M. S.; Mridha, M. A. U.; Islam, S. M. N.; Haque, S. M. S.; Shah, S. K.; Dhar, P. P. (Indian Forester, 2003)
The roots and rhizosphere soils of 14 leguminous forest tree seedlings were assessed at two nurseries in Bangladesh for the study of AM colonization and spore population. A great number of variations were observed in AM colonization in the roots and spore populations in the rhizosphere soils. Four genera were isolated and identified from the rhizosphere soils of different host species. The dominat genus was Glomus which was followed by Acaulospora, Entrophospora and Gigaspora. The possible role of indigenous AM fungi has been ensured for the primary establishment of nursery seedlings.<input id="gwProxy" type="hidden" /><input id="jsProxy" onclick="if(typeof(jsCall)=='function'){jsCall();}else{setTimeout('jsCall()',500);}" type="hidden" /><input id="gwProxy" type="hidden" /><input id="jsProxy" onclick="if(typeof(jsCall)=='function'){jsCall();}else{setTimeout('jsCall()',500);}" type="hidden" />